The influence of outdoor play spaces in urban parks on children's social anxiety - Bao, Yu; Gao, Ming; Luo, Dan; Zhou, Xudan (Frontiers in Public Health, 2022)
Urban green spaces are critical to the healthy development of children's social interactions and activities. However, the relationship between urban green spaces for children's activities and the alleviation of children's social anxiety remains unclear. This study aimed to explore the link between spatial characteristics and social anxiety in children. The assessment of children's play space and the level of social anxiety were obtained by self-report, OpenStreetMap captured the characteristic indicators of urban parks, and ArcGIS and SPSS carried out the mathematical analysis. To explore the coupling relationship between green space, play space, and social anxiety. The results showed that (1) both NDVI and 10-minute accessibility were significantly negatively related to children's social anxiety; (2) the diversity of service facilities, site materials, and the attractiveness and challenge of the environment were negatively related to children's social anxiety; (3) There are significant differences between activity types and social anxiety. These results provide design reference and a theoretical basis for improving the benefits of urban green space on children's health and well-being.